Distinct activity in prefrontal projections promotes temporal control of action - Xin Ding; Matthew A. Weber; Trevor C. Butler; Alexandra S. Bova; Stephanie G. Guerrero; Christopher M. Hunter; Rachel C. Cole; Hannah R. Stutt; Madison S. McMurrin; Mackenzie M. Spicer; Mackenzie M. Conlon; Shane A. Heiney; et al. (Proceedings of the National Academy of Sciences, 2026)
Prefrontal neurons exhibit diverse activity during cognitive functions such as working memory, attention, and timing; however, the importance of this heterogeneity is unclear. Our goal was to better understand the diversity of prefrontal activity through anatomical connectivity. We harnessed circuit-specific tools in mice to capture activity within prefrontal projections during interval timing, a highly translational cognitive process that requires working memory for temporal rules and attention to the passage of time to estimate a temporal interval of several seconds. We used neuronal recordings to capture prefrontal activity during interval timing, with major patterns characterized by monotonic time-dependent ramping over a temporal interval. We then leveraged retrograde viruses to interrogate prefrontal cortex (PFC) projections to the mediodorsal thalamus (PFC-MD) and the dorsomedial striatum (PFC-DMS). We report three main findings. First, circuit-specific fiber photometry revealed that PFC-MD and PFC-DMS activity encoded distinct temporal signals, with PFC-MD projections ramping down and PFC-DMS ramping up to interval timing response times. Second, circuit-specific inactivation revealed that suppressing PFC-DMS projections disrupted animals’ internal estimates of time. Third, circuit-specific single-nucleus RNA sequencing of projection-defined prefrontal neurons revealed distinct transcriptomic profiles of PFC-MD and PFC-DMS projections, with enrichment of cortical layer-associated genes as well as genes such as Cux2, Camk2n1, Htr4, and Foxp2 . These data suggest that differences in gene expression and connectivity distinguish prefrontal activity during interval timing. These findings advance our fundamental understanding of prefrontal function and dysfunction in human disease.